Nilai-Nilai Individu dan Remunerasi Terhadap Komitmen Organisasi Dalam Pendidikan Tinggi: Peran Mediasi Motivasi Kerja - Radiman, Radiman; Wahyuni, Sri Fitri; Lestari, Sri Puji (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Purpose – study aims to examine the effect of value and remuneration on organizational commitment through the work motivation of civil servant lecturers in private universities in Medan City.Methods – This research uses an associative quantitative approach. The research population consists of all civil servant lecturers of private universities in Medan City. The sample used in SEM (Structural Equation Modeling) research is a minimum of 180 samples. Data collection techniques include questionnaires and interviews. SEM PLS was used to analyze the data.Finding – The results showed that individual values and remuneration affect organizational commitment (p 0.05), and then work motivation also affects organizational commitment (p 0.05). Furthermore, personal values and remuneration influence organizational commitment through lecturers' work motivation in private universities in Medan (p 0.05).Originality/Novelty – This study examines individual values and remuneration more comprehensively as predictors of lecturers' organizational commitment and then explicitly explores the importance of work motivation as a mediator in the relationship between personal values, remuneration, and organizational commitment.Implications – This study has shown that work motivation mediates the influence of individual values and remuneration on organizational commitment. Recommendations for further research include analyzing or using work motivation variables as independent variables, not mediating variables. The results of this study can be used as a guide for strategic decision-making in higher education institutions and the development of theoretical studies in the field of organizational management.